The emerging culture of EU citizenship as "citizenship of rights" and the legal nature of the EU polity - Silveira, Alessandra (2016)
The current European crisis shows a crucial disjunction between the expectations of EU citizens and the institutional forms of political integration available to them. The crisis imposes challenges to the EU integration process, which sees its legitimacy questioned, above all in the eyes of the citizens of Member States undergoing intervention, who live with harsh restrictions and low expectations of improvement. EU citizens have never been so attentive to the developments of the EU integration – as testifies the rejection demonstrated in May 2014 elections to EU Parliament, now counting over 100 anti-EU voices. In this context, it is important to scrutinize whether the developing of an EU citizenship as “citizenship of rights” could perform some role in this scenario, putting it into perspective in order to grasp its effects on the legal nature of the EU polity. The status of EU citizenship is constructed around the paradigm of individual rights. Being an EU citizen basically means one is the holder of rights protected by the EU legal order – especially fundamental rights. Therefore, it is important to know to what extent the culture of rights has been strengthened by the change legal status of the Charter of Fundamental Rights of the European Union (CFREU) following the entry into force of the Lisbon Treaty in December 2009. In short, the text aims at knowing in which measure the fundamental rights dynamics in times of crisis affect the EU integration process itself.